Driving performance of underwater long-arm hydraulic manipulator system for small autonomous underwater vehicle and its positioning accuracy. (21st December 2017) - Yang, Chao; Wang, Yujia; Yao, Feng
A novel underwater long-arm manipulator (ULAM) and its improved small-flow hydraulic driving system (SHDS) are presented in this article for small autonomous underwater vehicle (AUV). In the process of manipulator design, a joint driving device consisting of linear hydraulic cylinder, three-bar linkage, and four-bar linkage mechanism is developed to allow the manipulator to be folded. Since the manipulator is much long, a small joint angle deviation would result in a large end-effector's position deviation. To solve the problem, a small-flow hydraulic driving device with circulation in closed loop is proposed. And in the long-arm manipulator, the cross-sectional area of manipulator is small. So the diameter of hydraulic pipeline installed inside the manipulator is limited, but the pipeline should also be long enough. In this case, it is common to cause large pressure loss in hydraulic system. And, rather than oil, water is selected as the hydraulic medium due to the low viscosity. In the hydraulic system design, a scheme with circulation in closed loop and improved sealing structure (consisting of O-ring and Glyd-ring) are developed to reduce the internal leakage and maintain a good end-effector's precision. In addition, the compressibility of water is relatively large, and it would bring bad impact on end-effector's precision. In this case, the vacuum-treated water is used and it has a good performance in the high-pressure condition. But in the low-pressure condition, the problem is still serious. In order to solve the problem, based on the "vacuum treatment, " a pre-pressurization pressure treatment is added for the vacuum-treated water. All the improved ways are verified by experiment results. Finally, the end-effector's positioning experiment and trajectory tracking experiment are conducted on manipulator and small AUV, so as to verify the effectiveness and feasibility of the ULAM.